Avaliação da prática do enfermeiro no âmbito da Estratégia Saúde da Família. - Sousa, Rosana Farias (2015)
The Primary Health Care (PHC) has been consolidated in Brazil through the Family Health Strategy, enabling compliance with the principles of SUS. Within this new context of work, nurses have assumed many responsibilities in the team and in the Basic Health Units. This study aims to evaluate nursing practice in the context of the Family Health Strategy of the municipality of São Luís-MA. The quantitative and descriptive approaches were used in this research. The population was constituted for 89 nurses. Working on the team for 6 months or longer was considered as an inclusion criteria. Those who were taking sick or training leave, refused to participate, were not reached after three attempts and those who didn t take part in the pilot study were excluded from the research. Two instruments were used for the data collection. The so-called Primary Care Assessment Tool (PCATool-Brazil), which measures the presence and extension of the 04 essential attributes (accessibility, continuity of care, completeness and care coordination) and the 02 derived attributes (focused attention on family, community orientation) of Primary Health Care, was used as an instrument in order to assess the issues relating to the essential and derived attributes from the PHC. The other instrument was a questionnaire with open and closed questions, which addressed issues related to the socialdemographic and professional profile and on the activities performed in practice. The data were organized using the EpiInfo software, 7.0 version, and the MicrosoftExcel worksheet. The descriptive analysis was carried out with relative and absolute frequencies. From the analysis of the data, it can be noted that the majority of nurses have average monthly income from 3 to 5 minimum wages (32.5 %), 41.6% of them work in strategy for 10 years or longer, 79.7% have got specialization, 58.4% are engaged in another professional activity and 86.5% have statutory labor bond. They are trained in several areas, but there are weaknesses in topics of great importance, such as: home care (21.3 %) and health education (41.6 %). The highest percentage was among those who rarely make home visits (48.3 %), demonstrating the need to strengthen this practice. Planning activities are performed, but a lack of knowledge about genogram (2.2 %) and ecomap (4.5 %) is observed. The educational activities are being accomplished, highlighting the lectures (97.8 %), with need for development of activities that will improve the interaction, listening and sharing of ideas. Regarding the attributes of Primary Health Care, low scores on the items accessibility (3.3), coordination - integration of care (5.0), completeness available services (6.0) and community orientation (4.4) were noticed. High scores stand out for the items continuity of care (6.6), coordination information system (8.0), integrality of provided services (6.6) and family orientation (7.3). The municipality of São Luís presented lower average essential (6,0), derived (5.6) and general scores (5.9) than the majority of Brazilian municipalities that used this tool. Although positive changes in posture and activities developed by the participants can be observed, it is still necessary that professionals and managers reflect on their practices, seeking to strengthen this new model in order to